The Relationship between Strategy of Work-life Quality and sustainable competitive advantage: A survey study on in Yemeni manufacturing industries - Maged Mohammed Abdullah Barahma; Mohammad Disomimba; Mohammed Ali Al-Awlaqi; Kalsom Ali (Journal Of System Management, 2024)
Non-Indexed Publication